1985
DOI: 10.1037/0022-006x.53.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral approach to classification of psychiatric patients using a competency model.

Abstract: Recent studies of hemisphere functioning among psychiatric patients have revealed an increasing level of impairment from depression to mania to schizophrenia, although clinical observation suggest that degree and type of impairment are substantially independent of psychiatric status. To test these hypotheses, £>-type factor analyses were performed on 25 neuropsychological variables for three samples of right-handed, adult psychiatric patients: an initial sample of 218 subjects; a within-laboratory replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Perhaps the most extensive documentation of this view comes from the study of Townes et al (1985) which identified six subgroups on the basis of Q-type factor analysis of a modified Halstead-Reitan battery, and reported that in five of the subgroups there was no relationship with psychiatric status. In support of comments made above, they state "...support is found for the hypothesis that patients with acute schizophrenic and affective psychoses vary across the entire continuum from no cognitive impairments to profound cognitive impairments.…”
Section: Complexities In Relating Neuropsychological To Psychiatric Dmentioning
confidence: 97%
See 1 more Smart Citation
“…Perhaps the most extensive documentation of this view comes from the study of Townes et al (1985) which identified six subgroups on the basis of Q-type factor analysis of a modified Halstead-Reitan battery, and reported that in five of the subgroups there was no relationship with psychiatric status. In support of comments made above, they state "...support is found for the hypothesis that patients with acute schizophrenic and affective psychoses vary across the entire continuum from no cognitive impairments to profound cognitive impairments.…”
Section: Complexities In Relating Neuropsychological To Psychiatric Dmentioning
confidence: 97%
“…Recently, Downloaded by [FU Berlin] at 12:18 06 July 2015 Goldstein and Shelly (1987) have attempted to apply cluster analysis in an attempt to define neuropsychologically based subtypes in a heterogeneous neuropsychiatric patient sample, using the Halstead-Reitan and Luria--Nebraska batteries, as well as the WAIS. Townes et al (1985) also applied an empirical, statistical classification system to categorize a large, international sample of neuropsychiatric patients.…”
Section: Neuropsychological Heterogeneitymentioning
confidence: 99%
“…On the other hand, there is evidence that specific cognitive deficits, such as distractibility, are stable in schizophrenia (Harvey, Docherty, Serper, & Rasmussen, 1990). Moreover, psychiatric patients in different settings, and in different countries, evince similar neurocognitive performance patterns (Townes et al, 1985). Besides, fluctuations in effort, motivation, and genera] proficiency may occur in traditional neurological samples.…”
Section: The Search For Brain Abnormalitiesmentioning
confidence: 99%
“…Fewer think to call upon neuropsychologists to map patients' cognitive strengths and weaknesses and relate them to the challenges of daily living. Clinical applications of those approaches to persons with severe psychiatric disability appear to be most recent (Diamant, 1981(Diamant, , 1985Diamant & Huijsman, 1982;Erickson & Binder, 1986;Spaulding, Storms, Goodrich, & Sullivan, 1986;Townes et al, 1985;Yozawitz, 1986).…”
Section: Lack Of Knowledgementioning
confidence: 99%